Analisis Pengaruh Harga Minyak Kelapa Sawit (CPO), Inflasi, Kurs Dan Suku Bunga Terhadap Harga Saham (Studi Empiris Pada Perusahaan Crude Palm Oil Di BEI Periode 2017-2021) - Faridatul Jannah; Luqman Hakim; Riyanti Riyanti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study was to analyze how the effect of crude palm oil prices, inflation rates, exchange rates and interest rates on stock prices in oil palm plantation companies listed on the Indonesia Stock Exchange for the period 2017-2021. The results of this study are expected to contribute in addition to researchers, practitioners and investors in helping them to make decisions, whether to sell, buy or hold their shares. The data used is secondary data in the form of annual reports of each issuer and statistical publications from the Indonesia Stock Exchange, Bank Indonesia and IndexMundi from 2017 to 2021. The sampling technique is purposive sampling with certain criteria. A sample of 10 Palm Oil Plantation (CPO) companies listed on the IDX during the observation period 2017-2021 was obtained. The analysis technique used is panel data regression analysis. The hypothesis was tested using t statistics to test the significance of the regression coefficient partially at a significance level of 95%. From the test results, all independent variables, namely palm oil prices, inflation, exchange rates, and interest rates, have an effect on stock prices in palm oil-producing plantation companies listed on the IDX in 2017-2021. Keywords: Palm Oil Prices (CPO), Inflation, Exchange Rates, Interest Rates and Stock Prices